'The Greatest Sale of Any Book Ever Printed in England, Except The Bible'? Robert Nelson's Companion for the Festivals and Fasts of the Church of England – A Neglected Devotional Classic. (1st June 2022) - Sharp, Richard
Although interest in the eighteenth-century Church of England has recently undergone a marked revival, little attention has been given to works of theological or devotional exposition. By examining one of the most widely circulated treatises of this kind, first published in 1703/4, this article demonstrates how nonjuring and conforming High Churchmen continued after 1688 to work together in a common defence of orthodox faith and order, sustaining a tradition of patristic scholarship inherited from the Caroline divines to oppose Christological heresies and to uphold teaching on ministry, sacraments and the proper relations of Church and State. The long publishing history of Robert Nelson's Companion for the Festivals and Fasts of the Church of England, which was regularly reprinted during more than a hundred years, also suggests how 'advanced' High Church doctrines regarding episcopacy, apostolic commission, ecclesiastical discipline, and the sacraments, may have been far more influential throughout the pre-Tractarian period than is commonly assumed.